2015
DOI: 10.3390/ijms16047273
|View full text |Cite
|
Sign up to set email alerts
|

Residue Asn277 Affects the Stability and Substrate Specificity of the SMG1 Lipase from Malassezia globosa

Abstract: Thermostability and substrate specificity are important characteristics of enzymes for industrial application, which can be improved by protein engineering. SMG1 lipase from Malassezia globosa is a mono- and diacylglycerol lipase (MDL) that shows activity toward mono- and diacylglycerols, but no activity toward triacylglycerols. SMG1 lipase is considered a potential biocatalyst applied in oil/fat modification and its crystal structure revealed that an interesting residue-Asn277 may contribute to stabilize loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…A, variant F278N retains the same overall structural architecture as the wild type, except for some minor small angle dislocation in strands β1, the preceding loop and β4. Residues 277 and 288 that were previously reported from our group to contribute to the stability and substrate specificity are in close vicinity of residue 278 and do not show any structural changes. The same is observed for the lid region (residues 101–119), which superimposes completely with that in the closed form (PDB ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3UUE) and displays relatively low B ‐factor (Fig.…”
Section: Resultssupporting
confidence: 58%
“…A, variant F278N retains the same overall structural architecture as the wild type, except for some minor small angle dislocation in strands β1, the preceding loop and β4. Residues 277 and 288 that were previously reported from our group to contribute to the stability and substrate specificity are in close vicinity of residue 278 and do not show any structural changes. The same is observed for the lid region (residues 101–119), which superimposes completely with that in the closed form (PDB ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3UUE) and displays relatively low B ‐factor (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Currently, many protein engineering methods have been developed to improve esterases (or lipases) properties, including substrate specificity [41,42], activity [43,44], thermostability [45], and enantioselectivity [46,47]. However, limited studies for enhancing alkali tolerance have been reported, especially based on structural information.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many protein engineering methods have been developed to improve esterases (or lipases) properties, including substrate speci city [41,42], activity [43,44], thermostability [45], and enantioselectivity [46,47]. However, limited studies for enhancing alkali-tolerance have been reported, especially based on structural information.…”
Section: Discussionmentioning
confidence: 99%